Pembelajaran Kartu Permainan Berbasis Profil Pelajar Pancasila untuk Meningkatkan Pemahaman Konsep Tema Persatuan dalam Perbedaan Siswa Kelas VI SD - Eni Harjanti; Iin Purnamasari; Sumarno Sumarno (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to determine the feasibility, practicality and effectiveness of playing card learning media based on the Pancasila Student Profile in learning theme 2 unity in differences in class VI SD. This type of research is research and development. The development is carried out referring to the Sugiyono development model. The subjects of the research trial were students of class VI SDN Kreyo in the academic year 2021/2022. Consisting of 6 students of class VI in the small group trial and 21 students of class VI in the large group trial. The results of the assessments of media experts and material experts indicate that the learning media for playing cards based on the Pancasila Student Profile is feasible to use with the